2013
DOI: 10.1103/physrevb.87.224409
|View full text |Cite
|
Sign up to set email alerts
|

Spin-state responses to light impurity substitution in low-spin perovskite LaCoO3

Abstract: We studied the spin-state responses to light impurity doping in low-spin perovskite LaCoO3 (Co 3+ : d 6 ) through magnetization and X-ray fluorescence measurements of single-crystal LaCo0.99M0.01O3 (M = Cr, Mn, Fe, Ni). In the magnetization curves measured at 1.8 K, a change in the spin-state was not observed for Cr, Mn, or Fe doping but was observed for Ni doping. Strong magnetic anisotropy along the [100] easy axis was also found in the Ni-doped sample. The fluorescence measurements revealed that the valence… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The M versus H curve of (Sc 0.95 Co 0.05 )CoO 3 was linear at 300 K up to 70 kOe. Deviations from the Brillouin function behaviour was observed in some doped LaCoO 3 samples [ 29 ]. Specific heat of (Sc 0.95 Co 0.05 )CoO 3 is given on figure 5 ; between 9 and 31 K, the data follow the equation C p / T = γ + β 1 T 2 with γ = 7.86(8) mJmol −1 K −2 and β 1 = 0.05452(17) mJmol −1 K −4 (the line in the inset of figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The M versus H curve of (Sc 0.95 Co 0.05 )CoO 3 was linear at 300 K up to 70 kOe. Deviations from the Brillouin function behaviour was observed in some doped LaCoO 3 samples [ 29 ]. Specific heat of (Sc 0.95 Co 0.05 )CoO 3 is given on figure 5 ; between 9 and 31 K, the data follow the equation C p / T = γ + β 1 T 2 with γ = 7.86(8) mJmol −1 K −2 and β 1 = 0.05452(17) mJmol −1 K −4 (the line in the inset of figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the substitution of 3d elements at the Co site in LaCoO 3 affects the spin state of nearby Co 3+ and exhibit various anomalous behaviors in the magnetic and transport properties [14,[42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…The more commonly identified magnetic moment of Fe 3+ in these lanthanum cobaltate systems is about 4 μ B , seen experimentally and simulated ( U = 4.0 and 5.4 eV, in the respective references) in LaFeO 3 , and between 3.7 and 4.3 μ B in La 0.875 Sr 0.125 FeO 3− δ and La 0.5 Sr 0.5 FeO 3− δ using a range of hybrid density functionals and two different Hubbard values . The spin of Co ranges from 0 to 0.39 μ B in all of our models except l4fo‐A where it is also 2.95 μ B on two of the four Co. Experimentally, the magnetic moment of Co 3+ is mostly speculated on and classified as low (out of “low,” “intermediate,” or “high”) for temperatures below 20 K and only on a light substitution of Co by Ni was an intermediate spin state induced in Co .…”
Section: Resultsmentioning
confidence: 87%
“…On increasing the Co:Fe ratio, no changes are observed for the electronic state of Co 3+ , except in one case: lc4fo‐A, in which there are only OFC groups present, a change from a low spin to an intermediate spin state is seen for two of the four Co 3+ ions. Tomiyasu et al showed for LaCoO 3 that a low substitution ratio (LaM 0.01 Co 0.99 O 3 ) can alter the local spin state of the Co 3+ ions. While for M = Fe, the experimental substitution ratio (forming far less than one OFC group per CoO 6 octahedron) was too low to observe a switch from low spin to intermediate spin, the 1:1 ratio of Co:Fe (forming six OFC groups per CoO 6 octahedron), according to our calculations, suffices.…”
Section: Discussionmentioning
confidence: 99%